Deep relief wood carving - Walker, Kevin (Atglen, Pa. : Schiffer Pub., 2015)
"This design for carving an intricate, three-dimensional dogwood branch sculpture in butternut lends itself well to wood carvers at most skill levels and can inspire an endless amount of future 3D relief projects" -- pages 4 of cover.
"Simple techniques for complex projects" - t.p.
Keywords: Wood-carving -- Technique; Relief (Decorative arts)